ChemInform Abstract: Facile Access to 2, 5‐Disubstituted‐4‐chloromethyl‐3‐iodofuran Derivatives via ICI‐Mediated Cyclization of 1‐Alkyl‐2‐alkynylallylic Alcohols. Issue 12 (14th March 2013) - Thongsornkleeb, Charnsak; Rabten, Wangchuk; Bunrit, Anon; Tummatorn, Jumreang; Ruchirawat, Somsak
Abstract The electrophilic agent I—Cl induces rapid cyclization of secondary enynyl alcohols (I) into dihalofurans (II).